2012
DOI: 10.1001/2012.jama.10893
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Physician-, Biomarker-, and Symptom-Based Strategies for Adjustment of Inhaled Corticosteroid Therapy in Adults With Asthma

Abstract: STHMA IS MANAGED BY CONsensus guidelines. 1,2 Disease activity varies daily, seasonally, and episodically, presumably related to airway inflammation. 3 Accordingly, asthma management requires periodic dose adjustments of controller medications, particularly inhaled corticosteroids. Adjustments have been based on (1) physician assessment of symp-For editorial comment see p 1036.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
209
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 183 publications
(214 citation statements)
references
References 23 publications
(45 reference statements)
1
209
1
3
Order By: Relevance
“…99 Four other studies also suggested no or weak association of FeNO and ACT in ICS users. [100][101][102][103] In children with atopic asthma, FeNO was significantly elevated in those with exercise induced reduction of FEV 1 (> 15%) with a negative predictive value (NPV) of 100% and a positive predictive value (PPV) of 28%. NPV and PPV for reported asthma symptoms within 2 weeks preceding the study were 96% and 26%.…”
Section: Children (Ages 5 To 18)mentioning
confidence: 99%
“…99 Four other studies also suggested no or weak association of FeNO and ACT in ICS users. [100][101][102][103] In children with atopic asthma, FeNO was significantly elevated in those with exercise induced reduction of FEV 1 (> 15%) with a negative predictive value (NPV) of 100% and a positive predictive value (PPV) of 28%. NPV and PPV for reported asthma symptoms within 2 weeks preceding the study were 96% and 26%.…”
Section: Children (Ages 5 To 18)mentioning
confidence: 99%
“…Mann PD 10 Provocative dose of mannitol causing a 10% fall in FEV 1 44 Mann PD 15 Provocative dose of mannitol causing a 15% fall in FEV 1 45 …”
Section: Labamentioning
confidence: 99%
“…However, other studies have suggested a more 31 muted response to inflammatory steroid titration in unselected asthmatic 32 patients 14,15 . 33 34 Price et al demonstrated retrospectively, in a primary care cohort, that 35 asthmatic patients with higher blood eosinophil counts fared worse in terms of 36 experiencing more severe exacerbations and poorer asthma control 16 .…”
mentioning
confidence: 99%
“…В другом исследовании, прове-денном среди пациентов с легким и среднетяжелым течением БА, было продемонстрировано, что время, в течение которого была отмечена неэффективность тера-пии, было примерно одинаковым и при назначении БДП и сальбутамола по потребности (в разных ингаляторах), и поддерживающей дозы ИКС, доза которых корректи-ровалась через 6-недельные интервалы в зависимости от решения врача [51]. В похожем исследовании, в кото-ром использовались отдельные ингаляторы для ИКС и КДБА для симптоматической терапии и регулярной терапии у детей [52], был показан сопоставимый уро-вень риска отсутствия эффективности терапии по срав-нению с регулярной терапией фиксированными дозами ИКС.…”
Section: комбинированнная терапия по потребности -сочетание симптоматunclassified